2012
DOI: 10.1128/aac.05998-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Morphological Effects of TDT 067 (Terbinafine in Transfersome) and Conventional Terbinafine on Dermatophyte Hyphae In Vitro and In Vivo

Abstract: TDT 067 is a novel, carrier-based dosage form of terbinafine in Transfersome (1.5%) formulated for topical delivery of terbinafine to the nail, nail bed, and surrounding tissue. We examined the effects of TDT 067 and conventional terbinafine on the morphology of dermatophytes. Trichophyton rubrum hyphae were exposed to TDT 067 or terbinafine (15 mg/ml) and examined under white light, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Subungual debris from patients treated with TDT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…The later finding, accumulation of lipid droplets was not observed in this study. Use of conventional terbinafine resulted in similar morphological changes, however, not as severe compared with TDT067 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The later finding, accumulation of lipid droplets was not observed in this study. Use of conventional terbinafine resulted in similar morphological changes, however, not as severe compared with TDT067 …”
Section: Discussionsupporting
confidence: 71%
“…A study on T. rubrum after treatment with 4‐amino‐3‐methyl‐I‐phenylpyrazolo‐(3,4‐ c ) isothiazole, G8, showed autolytic phenomena and acting by breaking down the endomembrane system including the ‘outer’ membrane . The effect of TDT067, a novel carrier‐based dosage form of terbinafine, on T. rubrum showed extensive ultrastructural changes such as cell collapsing, cell membrane deterioration and disruption of cellular materials and accumulation of lipid droplets . The later finding, accumulation of lipid droplets was not observed in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Elastic liposomes have been reported to improve skin penetration of various drugs (Mohammed et al, 2005), and they have been demonstrated for the delivery of drugs such as ibuprofen (Irfan et al, 2012), terbinafine (Ghannouma et al, 2012) and emodin (Lu et al, 2014). Transferosomes have also been reported in clinical studies to varying degrees of success.…”
Section: Improving Elasticity: Transferosomesmentioning
confidence: 99%
“…Topical treatment avoids the systemic effects of oral antifungal therapy, and may be preferred by physicians and patients. Topical agents approved for the treatment of mild to moderate fungal nail infection without matrix involvement include formulations based on ciclopirox (a hydroxypiridone) or amorolfine (a morpholine) or terbinafine (an allylamine)14. Ciclopirox, itraconazole, and terbinafine are approved in the United States and around the world for onychomycosis treatment, while amorolfine and fluconazole are approved in Europe9.…”
mentioning
confidence: 99%